Media and information literacy of young people: guidelines for public policy - Yu. V. Gnezdova; N. S. Sergienko (Управление)
Countering disinformation and strengthening the integrity of information require concerted efforts to increase the resilience of society in terms of threats in the information space, confronting them and recovering from them. In relation to young people, a set of measures isrequired not only to combat disinformation and strengthen the integrity ofinformation, but also to form competencies in the information ecosystem. The article shows that the resilience of society to information threats should become part of building a comprehensive or total protection system in which a young person can choose their role as checks and balances in the overall information ecosystem. The work considers the main risks and factors of influence of unreliable information resources on the younger generation. The article points to the urgent need to introduce accountable, transparent and flexible processes and structures of information resource management in public authorities. It is necessary to develop effective measures to respond to the threats posed by false information with their coordination in a specialised institute of public administration. As part of the preparation of the youth public policy, we need to develop and implement strategic approaches to ensuring the institutional architecture of information management for the younger generation.